The impact of palm oil price on the Malaysian stock market performance - Nordin, Sabariah; Nordin, Norhafiza; Ismail, Rusmawati (2013)
The performance of a stock market has always become the center of attention for market analysts and investors.Due to its significant role in the economy of a country, the performance of the stock market is always associated with the economic condition of a country.Because of that, this study intends to examine the impact of commodity prices in influencing the behaviour of the stock market index specifically by focusing on the palm oil prices.Since Malaysia is one of the major producers of palm oil, the behaviour of the palm oil price is expected to have an influence on the Malaysian stock market index. In pursuing the objective, we have adopted the bounds test approach to analyze the existence of cointegration relationship among the underlying variables of the Malaysian stock market index,interest rate, exchange rate and the price of palm oil. Using monthly data for the period of 1997M12 to 2012M9, results of an ARDL test indicates that all the variables employed are significant in influencing the Malaysian stock market index in the long run as well as in the short run.